Active Denitrification in the Hypolimnetic Water Column in Lake Kizaki - TERAI, Hisayoshi; YOH, Muneoki; SAIJO, Yatsuka (Japanese Journal of Limnology (Rikusuigaku Zasshi), 1987)
Denitrifying activities of the water column of Lake Kizaki were estimated by the acetylene blockage method. Active denitrification was detected in the developed anoxic water column and maximum activity was estimated as 2.0 μg-at N·l-1·day-1 at 24 m depth on 2 December 1984, where maximum nitrous oxide (N2O) accumulation (2.6 μg-at N·l-1) was also observed. Contribution of denitrification as N2O (N2O/(N2+N2O)) was found to be 34% to 49% of the total denitrification in some active denitrifying layers. When most active denitrification was observed, distribution of denitrifying bacteria in hypolimnion showed almost an exponential increase in number toward the lake bottom.